Advancement, Collaboration and Effective Combat in Low Resource Setting: Public Health Overview After One year of the Corona Virus Pandemic in Bangladesh - Afroz, T; Arman, KA; Khurshid, N; Rahman , S (Journal of Preventive and Social Medicine, 2022)
Background: Current Coronavirus pandemic causing millions of deaths and unfathomable damage of nations worldwide, especially in health sector. Bangladesh is dealing with the biggest catastrophic public health event of the history in a courageous and effective way. An evidence based narrative review has been undergone to scientifically describe Bangladesh government’s measures to encounter the Corona pandemic, so far. The aim of this study is to document the collaborative action of different ministries of Bangladesh government during this pandemic to understand the in-depth steps of the healthcare provision and disaster preparedness of the public-private-international association in a low-resource setting. Methods: A literature review over five months has been conducted to write down the evidential narration of the activities against the pandemic damage in Bangladesh. Keyword and result based literatures and current media reports searched has been done. Selection criteria: Both online and offline reports, descriptive articles, governmental portal and ministerial websites were reviewed. The description is reported specifically based on the documents directed by government to fight against COVID-19 from the beginning of the pandemic till the writing period. Findings and discussion: In spite of the resource constraints, government of Bangladesh has been able to limit the damage in an optimal level. The inter- and- inter ministerial functional proposition and collaboration in national and international stakeholders initiated and sustained by the government strengthen the shield against the Coronavirus invasion. Conclusion: The sufferings brought by the pandemic knows no bound. The pandemic damage and ruin are unspeakable and undeniable at the same time. It is time to observe the positivity and critically appreciate the efforts taken by the current governmental authority to make a constructive remark for present situation, and be prepare for future building of the nation. JOPSOM 2021; 40(1): 66-71